Wildland Firefighting: Adverse Influence on Indices of Metabolic and Cardiovascular Health. Issue 3 (March 2019) - Coker, Robert H.; Murphy, Carl J.; Johannsen, Michelle; Galvin, Grant; Ruby, Brent C.
Abstract : Objective: The purpose of this study was to evaluate pre- and postseason measures of body composition, skeletal muscle, and blood parameters/liver lipid in wildland firefighters (WLFF) over the fire season. Methods: Alaskan WLFF ( N  = 27) crews were evaluated pre- and postwildfire season, which included 63 ± 10 operational days. Body composition, thigh muscle area, and liver lipid were quantified using dual-energy radiograph absorptiometry and magnetic resonance imaging, respectively. Blood metabolic and lipid panels were also collected and analyzed. Results: Total body, fat, and visceral fat mass increased from pre- to postseason ( P  < 0.05). Total cholesterol, LDL, and total globulin also increased ( P  < 0.05). There was a trend ( P  = 0.06) towards an increase in intrahepatic lipid. Conclusions: The observed maladaptive changes in adipose tissue, blood lipids, and hepatic function may reflect adaptations/consequences to occupational demands/conditions and warrant evaluation of appropriate countermeasures.